Determining the severity and prevalence of cybersickness in virtual reality simulations in psychiatry - Amanda Ng; Mai Inagaki; Rachel Antinucci; Sanjeev Sockalingam; Petal S. Abdool (Advances in Simulation)
Abstract Background The rise in virtual reality (VR) applications in healthcare has introduced immersive VR simulations as a valuable training tool for medical professionals. Despite its advantages, VR use can induce cybersickness, characterized by symptoms such as nausea and disorientation. This study examines the relationship between cybersickness and the degree of physical movement in VR simulations used for psychiatric education. Methods The study involved two VR simulations offered at a Canadian mental health hospital: an opioid overdose response (OO) (high movement VR) and suicide risk assessment (SRA) (low movement VR). Participants’ experiences were measured using the Simulator Sickness Questionnaire (SSQ) before and after the training sessions. A nonparametric Mann–Whitney U-test was conducted to compare SSQ scores between the two VR simulations. Results A total of 91 participants, including healthcare practitioners and students, were involved. The mean SSQ score for the OO training was 4.59/48 (SD = 5.78), while for the SRA, it was 3.10/48 (SD = 3.48). Mann–Whitney U-test revealed a significant increase in nausea scores in OO simulation compared to SRA simulation (p = 0.0275), with higher nausea reported in the OO simulation. No significant increases were found in oculomotor symptoms. Conclusions Participants in the OO training experienced higher levels of nausea compared to those in the SRA simulation, likely due to increased need for physical movement. These findings underscore the importance of considering the degree of physical movement in the VR training design, specifically the educational value of these movements and the risk of cybersickness negatively impacting VR tolerability for learners.